Health disparities and intellectual disabilities - Hatton, Christopher; Emerson, Eric (International review of research in developmental disabilities., 2015)
International Review of Research in Developmental Disabilities is an ongoing scholarly look at research into the causes, effects, classification systems, and syndromes of developmental disabilities. Contributors come from wide-ranging perspectives, including genetics, psychology, education, and other health and behavioral sciences. Provides the most recent scholarly research in the study of developmental disabilities. A vast range of perspectives is offered, and many topics are covered. An excellent resource for academic researchers.